2007
DOI: 10.1002/jor.20468
|View full text |Cite
|
Sign up to set email alerts
|

A novel injectable scaffold for cartilage tissue engineering using adipose‐derived adult stem cells

Abstract: Articular cartilage has a limited self-regenerative capacity. Thus, treatment of cartilage lesions is a major challenge. Tissue engineering using a variety of biomaterials is a promising solution to the problem of cartilage damage. In this in vitro study, we investigated the effect of the presence of cartilage-tissue chondroitin-sulfate (CS) in a fibrin scaffold on the differentiation of adipose-derived adult stem cells (ADAS cells) into chondrocytes. Isolated rabbit ADAS cells were cultured in fibrin matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…In accordance with previous studies demonstrating the chondrogenic potential of ASCs (46)(47)(48), the ECM produced by ASCs seeded within the large PCL hemispheres stained positively for cartilage-specific macromolecules, which accumulated on all scaffolds over time (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies demonstrating the chondrogenic potential of ASCs (46)(47)(48), the ECM produced by ASCs seeded within the large PCL hemispheres stained positively for cartilage-specific macromolecules, which accumulated on all scaffolds over time (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
“…3 McGowan Institute for Regenerative Medicine, Pittsburgh, Pennsylvania. 4 Division of Plastic and Reconstructive Surgery, University of Pittsburgh, Pittsburgh, Pennsylvania. et al evaluated the effect of ASCs in the treatment of induced tendinitis of the superficial digital flexor tendon in horses and observed increased perivascular inflammatory infiltrate, fibroblastic density, and qualitative healing improvement of tendon extracellular matrix.…”
Section: De Mattos Carvalhomentioning
confidence: 99%
“…Adipose tissue may be harvested from patients in a minimally invasive manner and provides a large quantity of autologous cells. 4 Adipose-derived stem cells (ASCs) derived from discarded human adipose tissue have many properties such as immunocompatibility and multipotency, rendering the cells ideal for regenerative medicine applications, such as cartilage, bone, soft tissue, and nerve repair. 5 Further, MSCs derived from adipose tissue possess the highest proliferation and differentiation potential, followed by MSCs derived from bone marrow and cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…36,45,48,49 As an alternative source of chondrogenic progenitor cells, adult stem cells derived from a variety of tissues have been investigated for cartilage tissue engineering. [50][51][52][53] In particular, recent studies have shown the presence of an abundant source of multipotent adult stem cells that are easily accessible from subcutaneous adipose tissue via liposuction and are capable of chondrogenesis. 54,55 During in vitro expansion, adipose-derived stem cells (ASCs) can maintain a stable undifferentiated status without change in telomerase activity over nine passages, 56 suggesting that these cells can be expanded as an abundant cell source without loss of multipotency.…”
mentioning
confidence: 99%